2020
DOI: 10.21037/tcr.2019.11.30
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of PI3 and HLA-DOB as potential prognostic predicators for ovarian cancer

Abstract: Background: The outcomes of ovarian cancer patients are very poor, therefore it is necessary to find prognostic biomarkers and explore the potential underlying molecular mechanisms of ovarian cancer.Methods: In this study, a gene expression microarray data set covering 562 ovarian serous cystadenocarcinomas and 12,042 genes was downloaded from The Cancer Genome Atlas (TCGA) database.For each candidate gene, samples were allocated into a "high group" or a "low group" according to the expression level. The overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The peptidase inhibitor 3 ( PI3 ) is a serine protease inhibitor with known anti-inflammatory, antimicrobial, and immune-modulatory properties [ 48 ] and was shown to be downregulated during ovarian tumorigenesis, while its residual expression is predictive of recurrence [ 49 ]. Two recent studies independently identified PI3 as a potential prognostic biomarker for OC [ 50 , 51 ]. PLXNA1 encodes a co-receptor for semaphorins and plays a role in axon guidance, invasive growth, and cell migration [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peptidase inhibitor 3 ( PI3 ) is a serine protease inhibitor with known anti-inflammatory, antimicrobial, and immune-modulatory properties [ 48 ] and was shown to be downregulated during ovarian tumorigenesis, while its residual expression is predictive of recurrence [ 49 ]. Two recent studies independently identified PI3 as a potential prognostic biomarker for OC [ 50 , 51 ]. PLXNA1 encodes a co-receptor for semaphorins and plays a role in axon guidance, invasive growth, and cell migration [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the study screening gene pathways were very different, some of our constructed risk model genes were also screened as prognostic predictors of ovarian cancer in other ovarian cancer risk model studies, which further side validating the high accuracy of our constructed model: Fc Gamma Binding Protein (FCGBP) [18],Calcium Voltage-Gated Channel Subunit Alpha1 C (CACNA1C) [19],Ubiquitin D(UBD) [20,21],Peptidase Inhibitor 3(PI3) [22,23],Interferon Stimulated Exonuclease Gene 20 (ISG20) [24][25][26],A-Kinase Anchoring Protein 12(AKAP122) [26,27],Ribosomal Protein S6 Kinase A2(RPS6KA2)[28],C-X-C Motif Chemokine Ligand 11(CXCL11) [21,[29][30][31][32][33][34],Transient Receptor Potential Cation Channel Subfamily V Member 4(TRPV4) [35],Cholesterol 25-Hydroxylase(CH25H) [23,36],Solute Carrier Family 4 Member 8(SLC4A8) [37] However, the following genes have not been identi ed in ovarian cancer studies: Translocase Of Outer Mitochondrial Membrane 20 Like (TOMM20L), C-C Motif Chemokine Receptor 7(CCR7), Phosphatidylinositol Glycan Anchor Biosynthesis Class S(PIGS), Syntaxin 18(STX18), Carboxymethylenebutenolidase Homolog (CMBL)have not been found to be studied in ovarian cancer. This is the rst study to type ovarian cancer based on DDR-related genes and to investigate the prognostic relevance of genes that differ between types in ovarian cancer.…”
Section: Discussionmentioning
confidence: 76%
“…In recent studies, researchers have found its tight connection with reproductive system cancers such as OC ( 25 ), breast cancer ( 49 ), and cervical cancer ( 23 ). Previous studies have already found the correlation between elafin upregulation and an unfavorable prognosis of OC patients, but the particular reason why the relevance of elafin expression and OS varies in different stages of tumorigenesis is not clear enough ( 24 , 50 ). Moreover, elafin-related immune infiltration requires more attention.…”
Section: Discussionmentioning
confidence: 99%